Revista de la Escuela Superior de Guerra ; no. 359/1965 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (1965)
Ejemplar: Revista de la ESG. Año 43, no. 359 (mayo-jul. 1965). p. 142.